Movimento Poetas na Praça: uma poética de ruptura e resistência - Silva, Antonio de Pádua de Souza e (2008)
Poetry is a literary phenomenon that, besides man and his language since earlier times until nowadays and will beside him while humanity, exists. However, each time has a particular manifestation to this kind of human language. At the 1970s, in Brazil, there was a kind of poetry that was produced and sailed out of conventional patterns, called marginal poetry; a kind of poetry that, as kind of art, answer to its historical time and, as soon as it happened to 1922s Modernism, 1950s Concretism and 1960s Tropicalism, conquered popular appreciation all over the country. This kind of poetry first work was 26 poetas hoje (26 poets today), a text anthology of texts by 26 authors who lived at Rio de Janeiro or Sao Paulo, organized and published by Heloísa Buarque de Holanda. At the end of the 1970s and longing all the 1980s, a group of young poets decided to put poetry at squares, near people; thus, Movimento Poetas na Praça (Poets at Squares Movement) grew up. Their central stage was Praça da Piedade (Piety Square), in Salvador, capital of Bahia state, where they joined to declaim their own and other author s poems, convoking people to a genial performance, as it used to happen on Medieval times. Movimento Poetas na Praça s founders were Antonio Short, Ametista Nunes, Eduardo Teles and Gilberto Costa, whose texts compose this work corpus. This poetry, called marginal, made angry some others poets, literary critics and scholars who called it sub-literature only because it doesn t follow official literary patterns and values all those who propose themselves as poets. Analyzing some poems composed by those poets, this study aims to offer a brief outline of this movement and contribute to finish the prejudice directed against this group of poets and their literary production